Combined Tumor Sequencing and Case-Control Analyses of RAD51C in Breast Cancer. (5th April 2019) - Li, Na; McInerny, Simone; Zethoven, Magnus; Cheasley, Dane; Lim, Belle W X; Rowley, Simone M; Devereux, Lisa; Grewal, Norah; Ahmadloo, Somayeh; Byrne, David; Lee, Jue Er Amanda; Li, Jason; et al.
Abstract: Background: Loss-of-function variants in RAD51C are associated with familial ovarian cancer, but its role in hereditary breast cancer remains unclear. The aim of this study was to couple breast tumor sequencing with case-control data to clarify the contribution of RAD51C to hereditary breast cancer. Methods: RAD51C was sequenced in 3080 breast cancer index cases that were negative in BRCA1/2 clinical tests and 4840 population-matched cancer-free controls. Pedigree and pathology data were analyzed. Nine breast cancers and one ovarian cancer from RAD51C variant carriers were sequenced to identify biallelic inactivation of RAD51C, copy number variation, mutational signatures, and the spectrum of somatic mutations in breast cancer driver genes. The promoter of RAD51C was analyzed for DNA methylation. Results: A statistically significant excess of loss-of-function variants was identified in 3080 cases (0.4%) compared with 2 among 4840 controls (0.04%; odds ratio = 8.67, 95% confidence interval = 1.89 to 80.52, P < .001), with more than half of the carriers having no personal or family history of ovarian cancer. In addition, the association was highly statistically significant among cases with estrogen-negative ( P <. 001) or triple-negative cancer ( P < .001), but not in estrogen-positive cases. Tumor sequencing from carriers confirmed bi-allelic inactivation in all the triple-negative cases and was associated with high homologous recombination deficiency scores and mutational signature 3 indicating homologous recombination repair deficiency. Conclusions: This study provides evidence that germline loss-of-function variants of RAD51C are associated with hereditary breast cancer, particularly triple-negative type. RAD51C -null breast cancers possess similar genomic and clinical features to BRCA1 -null cancers and may also be vulnerable to DNA double-strand break inducing chemotherapies and poly ADP-ribose polymerase inhibitors.